Oncolytic Reovirus in Canine Mast Cell Tumor - Hwang, Chung Chew; Umeki, Saori; Kubo, Masahito; Hayashi, Toshiharu; Shimoda, Hiroshi; Mochizuki, Masami; Maeda, Ken; Baba, Kenji; Hiraoka, Hiroko; Coffey, Matt; Okuda, Masaru; Mizuno, Takuya (PloS one, 2013)
The usage of reovirus has reached phase II and III clinical trials in human cancers. However, this is the first study to report the oncolytic effects of reovirus in veterinary oncology, focusing on canine mast cell tumor (MCT), the most common cutaneous tumor in dogs. As human and canine cancers share many similarities, we hypothesized that the oncolytic effects of reovirus can be exploited in canine cancers. The objective of this study was to determine the oncolytic effects of reovirus in canine MCT in vitro, in vivo and ex vivo. We demonstrated that MCT cell lines were highly susceptible to reovirus as indicated by marked cell death, high production of progeny virus and virus replication. Reovirus induced apoptosis in the canine MCT cell lines with no correlation to their Ras activation status. In vivo studies were conducted using unilateral and bilateral subcutaneous MCT xenograft models with a single intratumoral reovirus treatment and apparent reduction of tumor mass was exhibited. Furthermore, cell death was induced by reovirus in primary canine MCT samples in vitro. However, canine and murine bone marrow-derived mast cells (BMCMC) were also susceptible to reovirus. The combination of these results supports the potential value of reovirus as a therapy in canine MCT but warrants further investigation on the determinants of reovirus susceptibility.